The Importance of Foreign Experience in the Development of Culture and Arts Management - qizi, Karimova Ezoza Nuriddin; ogli, Mominmirza Kholmominov Zakir (Research Parks Publishing LLC, 2023)
This article provides information about the management of art and culture, which is developing all over the world, and the importance of using the experience of foreign countries in its study. Also, the objects that prove the development of art management in Great Britain, the USA, Colombia, and Spain are given as examples. As a conclusion, the name of the books related to the field in a foreign language that should be translated is mentioned. As a conclusion, the name of the books related to the field in a foreign language that should be translated is mentioned.